ANALYSIS OF THE IMPLEMENTATION OF STRATEGIC MANAGEMENT IN INCREASING HOSPITAL COMPETITIVENESS IN THE DIGITAL ERA - Bahari, Eko Satrio; Ellyana Ellyana; Yani Restiani Widjaja; Purwadhi, Purwadhi (Bajang Institute, 2024)
Research Objectives: This study aims to analyze the implementation of strategic management in enhancing hospital competitiveness in the digital era, identify critical success factors, and explore the challenges faced by hospitals in their digital transformation process. Research Methods: The study employs a mixed-method approach, combining quantitative methods through surveys of 200 middle and senior managers from 50 hospitals in Indonesia, and qualitative methods through in-depth interviews with 20 hospital executives. Data analysis involves structural equation modeling (SEM) for quantitative data and thematic analysis for qualitative data. Research Results: Effective implementation of digital strategic management has been shown to improve hospital competitiveness through increased service innovation, improved quality of care, and enhanced patient satisfaction. Critical success factors include strong top management support, technological readiness, and a culture of innovation. Key challenges include resistance to change, budget constraints, and digital competency gaps. The study proposes a